2004
DOI: 10.1080/0887044031000148246
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative body-related comments and their relationship with body dissatisfaction in middle-aged women

Abstract: We examined the relationship between body-related comments recalled across the life span and current body esteem among 898 54-year-old female participants from the MRC National Survey of Health and Development. A significant effect of negative comments while growing up, which was independent of comments from partner, suggests an enduring adverse impact of these early comments on midlife body esteem. There was no evidence that the detrimental effect of negative comments recalled while growing up could be revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 24 publications
2
36
0
1
Order By: Relevance
“…Particularly insidious is the exposure to sexualized media environments that objectify women, which has been linked to the development of adolescent girls' and boys' notions of women as sex objects (American Psychological Association, Task Force on the Sexualization of Girls 2007; Grogan and Wainwright 1996;Harper and Tiggemann 2008;Peter and Valkenberg 2007;Ward and Friedman 2006). Moreover, these experiences of objectification endure in the lives of women, with research from a nationally representative cohort of middle-aged women in Britain demonstrating that body-related comments received in childhood continue to be associated with low body esteem across the life span (McLaren et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…Particularly insidious is the exposure to sexualized media environments that objectify women, which has been linked to the development of adolescent girls' and boys' notions of women as sex objects (American Psychological Association, Task Force on the Sexualization of Girls 2007; Grogan and Wainwright 1996;Harper and Tiggemann 2008;Peter and Valkenberg 2007;Ward and Friedman 2006). Moreover, these experiences of objectification endure in the lives of women, with research from a nationally representative cohort of middle-aged women in Britain demonstrating that body-related comments received in childhood continue to be associated with low body esteem across the life span (McLaren et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…Abraczinskas et al (2012) found that negative weight-related and eating-related comments from one's parents can affect one's drive for thinness and encourage bulimic symptomatology in teenagers. However, in a dominant atmosphere of negative feedback about one's body, positive or even neutral feedback may lead to improved body image (Herbozo and Thompson 2006;Mclaren et al 2004). Naturist activities, in which individuals spend time naked in the company of non-intimate others, also involve being seen naked by a large number of people in a relatively non-judgemental context, which might lead to less dissatisfaction with one's body.…”
Section: Why Should Naturism Have Positive Psychological Effects?mentioning
confidence: 99%
“…Extending prior research on cosmetic surgery attitudes (Brown, Furnham, Glanville, & Swami, 2007;Henderson-King & Henderson-King, 2005;Sarwer et al, 2005;, the present study investigates objectification theory variables (i.e., sexual objectification, self-surveillance, body shame) as a specific set of interpersonal and intrapersonal factors that may be associated with womenÕs endorsement of cosmetic surgery as an acceptable means of changing their physical appearance. Specifically, this cross-sectional investigation examines the relationship between objectification theory variables and cosmetic surgery attitudes among a sample of women living in the U.K., a cultural context within which women consistently report high levels of appearance concerns, sexual and self-objectification, and interest in cosmetic surgery (Calogero, 2009;Calogero, Park, Rahemtulla, & Williams, 2010;Calogero & Thompson, 2009a;Dittmar et al, 2000;Grogan 2008;McLaren, Kuh, Hardy, & Gauvin, 2004;Puwar, 2004;Swami, Chamorro-Premuzic, Bridges, & Furhman, 2009). This research provides a new test and application of objectification theory to the understanding of womenÕs lived experiences in westernized societies.…”
Section: Introductionmentioning
confidence: 99%